From Aversion to Affinity: India's Standpoint in the Trade-Related Aspects of Intellectual Property Rights Negotiations - Tania Delavita Malik (Global South Review, 2019)
When the issue of protecting IPRs was brought to the GATT in 1986, India claimed it as unnecessary given the costly administrative affairs in domesticating the agreement and the difference in countries’ levels of development. However, the standpoint of India altered significantly in the Doha Round. India did not only agree to adopt the TRIPS Agreement but also proposed the protection of broader aspects of IPRs, to also include GRTKF. The adoption of these significantly different viewpoints poses the puzzle that this article seeks to explain. In doing so, this article uses two-level game theory by Robert D. Putnam to analyze both domestic and international pressures that simultaneously pushed India to alter its position on IPR protection at WTO. It analyses the actions taken by governmental actors, NGOs, and business groups at both domestic and international levels. The findings demonstrate that India adopted different standpoints because of domestic demands, precisely those of the pharmaceutical companies and pro-indigenous-people NGOs, while different set of actors, especially developing countries, at international level also supported it. The supports from these actors exceeded the pressures from big pharmaceutical companies from developed countries and the developed countries themselves. By arguing this, this article thus suggests that India, as a developing country, has been able to advocate the demand of domestic interests in the face of massive international pressures.